EFFET DU VIEILLISSEMENT SUR LA DEFORMATION MECANIQUE DE FILM EN POLYETHYLENE. - BENMILOUD NOURELHOUDA; Monsieur : CHABIRA S. FOUAD Encadreur Professeur UATL –Laghouat (Bibliotheque centrale -Unversite de Laghouat, 2017)
Low density polyethylene (LDPE) films having semicrystalline morphology have been used to highlight the ageing effect on the relationship between LDPE film structure and its mechanical behavior. Four different subjects have been addressed are: 1) morphological analysis, 2) orientation dependence and controlled deformations, 3) creep-recovery behavior and loading effect, 4) ageing effects on the creep-recovery behavior. For the first topic, the surface morphological changes due to exposure have been analyzed by AFM and FESEM, crystallinity has been calculated by DSC and XRD experiments. However DSC allowed the determination of lamellar thickness and its distribution which were affected by ageing. The three following topics, tensile tests, deformation under controlled deformation, and creep tests, were performed not only at different angles of the film plane with respect to the main directions machine direction (MD), but also at different ageing stages of exposure except the topic 5.0 which was the focus of the orientation and loading only. In the structural and morphological study (chapter 2.0), DSC, XRD, AFM, and FESEM experiments were conducted for pristine and altered samples having different morphologies. it was shown that natural weathering leads to a complex photochemical mechanism by increasing crystalline concentration (calculated by XRD and DSC), either by the lamellar thickness or by nucleating new crystallite via a chemo- crystallization process, also it was found that crystallinity increase calculated with XRD agreed with DSC. AFM and FESEM were very efficient for the surface morphology analysis, the roughness and the height valley increase in reason of the increase of the surface crystalline zones, also it has been found that the peaks-spacing and Rrms which logically progress inversely, followed an evolution that obeys to linear mathematical relationships. In the stress-strain deformation study (chapter 3.0), samples were stretched under controlled strain rates at 0°, 45°, and 90° angles of the film plan with respect to the original direction (MD). The relative elongation and true strain are strongly dependent on the deformations angles; the true strain is greater in the 45° stretch followed by 90° then 0°. Furthermore, planes delimited by the marks remain uniform during the whole deformation. The lateral contraction is significant in the 45° stretch. iii Furthermore, ageing provokes a decrease in the true strain and lateral contraction. The Poisson’s ratio was determined and found to be independent to orientation and ageing. In large stress-strain tests, samples are stretched in the two main directions (MD and TD), a contributive demonstration of several relationships between the microscopic deformation mechanisms and the induced morphological changes and macroscopic tensile properties. Stretching parallel to the MD results in lamellar separation, followed by break-up of the crystalline lamellae via chain slip. Stretching perpendicular to the MD causes the crystalline lamellae to break-up or rupture by chain pull-out. Furthermore, ageing decreases the properties at the break, the tensile behavior deformed with two strain rates for a given ageing state is different. In loading and orientation effect on the creep-recovery behavior study (chapter 4.0), samples have been tested at the two main directions of the film plan (MD and TD). The creep deformation and creep rate is higher in TD. The creep resistance and the different creep-recovery deformations decreases with increasing applied stress, so the minimum strain rate increases. The linear-non-linear viscoelastic transition is around 7.6 MPa and lifetime of each deformation is determined. The recovered elastic portion decreased with increasing applied stress. In the ageing effect on the creep-recovery behavior study (chapter 5.0), samples have been tested at different orientation, applied stress, and ageing stages. ATR-FTIR was very efficient to reveal each of the microstructural and morphological changes; crosslinking and chain scission reactions affect adversely the mechanical properties (tensile tests) leading to a global material stiffening, the increase in crystallinity calculated from ATR-FTIR agreed with those of DSC and XRD. The creep resistance increases with exposure time for both directions, however the minimum strain rate ( ) is higher in the TD. The vinylidenes present a close relationship with viscous flow. The viscous character of the material is strongly lowered not only by crosslinking and chain scissions, but also by crystallinity. The instantaneous (a) and the final recoveries ( , ), diminish with increasing exposure time.